Overview: the opportunity of BIM in railway. Issue 2 (7th May 2019) - Bensalah, Mounir; Elouadi, Abdelmajid; Mharzi, Hassan
Abstract : Purpose: The authors will give an overview of the railway market, with a focus on Morocco, before seeing the challenges to face, before listing some benefits of rail links in terms of development, ecology, security, space management, etc. The authors will then give an overview of the development of BIM, its benefits, risks and issues. The purpose of this paper is to verify that the BIM can provide the railway with the tools to face some of its challenges and improve its productivity. Design/methodology/approach: This paper is part of our research project on the integration of BIM in railway, which is the result of a partnership between Colas Rail Maroc and the ENSAK of the Ibn Tofail University of Kenitra. The objective of this paper is mainly to confirm that the integration of BIM with the railway, through a theoretical and practical study, can have positive impacts. To do this, our methodology consists in studying briefly the development of the railway, the need to improve the budgets and schedules of the projects, to increase the productivity, before showing the advantages of the BIM in the sector of the Architecture, Engineering and Construction (AEC). The study of feedback from railway projects (chosen for their date of completion – beyond 2014, their size, their geographical situation in several countries and for the availability of literature in a new field) will confirm the initial hypotheses. Among the projects studied will be a project that has been the subject of an article written by the authors of this paper. In the discussion of the results, the authors will focus on the benefits, risks and limitations of integrating BIM into the railway. In conclusion, the authors are laying the groundwork for future research in the field. Findings: The cases study discussed in this paper and previous research confirms the hypotheses of the literature. The integration of BIM into railway projects can have several advantages: collaboration, time saving, cost optimization, prevention of conflicts between networks, construction before construction, optimization of facility management, improvement of the quality of works, prefabrication. They also allowed us to illustrate the risks (status and appropriation of the BIM model, lack of standardization of versions or software and lack of understanding of the basics of schedules and specifications) and limitations (lack of feedback, lack of adaptability and convergence of tools). These experiences have also shown that the use of BIM is not just a technological transition, but a revolution in the project management process, which requires several key success factors (participation of all, commitment, change management and adoption of the collaborative approach). Visualization, collaboration and conflict elimination are the three main chapters where the benefits of BIM can be organized. In fact, there is a lot of intersection between these chapters, but they have been chosen as the main ideas around which all the benefits can be better understood. Visualization primarily addresses the benefits to an individual and improving one's personal understanding as a result of using BIM. The collaboration refers to the cooperative action of several team members, which is encouraged and facilitated by BIM. Conflict elimination mainly concerns project-related benefits, such as conflict reduction, waste, risks, costs and time. For railway infrastructure projects, the main purpose of using BIM is to improve the design integration process, internal project team communication and collision detection to eliminate risk of rehabilitation. Research limitations/implications: The application of the BIM process in railway infrastructure requires constant improvement. This concerns the development of libraries and the models available to all users in order to encourage the development of this methodology and, consequently, its use of information throughout the life cycle of an infrastructure work. Practical implications: The case study of real projects incorporating BIM confirms the results of the literature review. The benefits of integrating BIM into rail projects are multiple and proven: cost control, decision support, avoids extra work due to design errors, improves detection of interface problems, improves planning of vision, help with prefabrication and facility management, etc. Finally, the BIM process is able to overcome delays in procedures slowing the development of the construction industry in many countries, especially in Morocco, because of the slowness of design (or downright bad design). Social implications: The integration of BIM into rail is becoming a global trend. This integration requires government decisions and a maturation of technology and tools. The authorities of some developed countries studied (Sweden, UK, France, Germany) in the railways, at different stages of implementation, are adopting BIM in the process of setting up new railway projects. This political impulse is still behind in southern countries, such as Morocco. The trend and the data collected indicate an adoption between 2020 and 2030 of BIM in all/some AEC projects in developed countries. This will have an impact on other countries that will soon be doing the same, especially in the railway sector to adopt the BIM. Originality/value: As part of the realization of this paper, we proceeded to the implementation of an electrical substation as part of the project to build 40 electric traction substations built by Colas Rail on behalf of ONCF.